Facing the future: challenges and opportunities in adoptive T cell therapy in cancer. (3rd August 2019) - Magalhaes, Isabelle; Carvalho-Queiroz, Claudia; Hartana, Ciputra Adijaya; Kaiser, Andreas; Lukic, Ana; Mints, Michael; Nilsson, Ola; Grönlund, Hans; Mattsson, Jonas; Berglund, Sofia
ABSTRACT: Introduction : In recent years, immunotherapy for the treatment of solid cancer has emerged as a promising therapeutic alternative. Adoptive cell therapy (ACT), especially T cell-based, has been found to cause tumor regression and even cure in a percentage of treated patients. Checkpoint inhibitors further underscore the potential of the T cell compartment in the treatment of cancer. Not all patients respond to these treatments; however, many challenges remain. Areas covered : This review covers the challenges and progress in tumor antigen target identification and selection, and cell product manufacturing for T cell ACT. Tumor immune escape mechanisms and strategies to overcome those in the context of T cell ACT are also discussed. Expert opinion : The immunotherapy toolbox is rapidly expanding and improving, and the future promises further breakthroughs in the T cell ACT field. The heterogeneity of the tumor microenvironment and the multiplicity of tumor immune escape mechanisms pose formidable challenges to successful T cell immunotherapy in solid tumors, however. Individualized approaches and strategies combining treatments targeting different immunotherapeutic aspects will be needed in order to expand the applicability and improve the response rates in future.